Screening And Treatment Of Pregnant In Chlamydia Trachomatis In Lima, Peru - Aparcana, Pedro García (2019)
Objectives. The study aims to implement a test for the detection ande treatment of chlamydia during antenatal care, determining the acceptability and feasibility of universal screening and to measure adherence of the patient and her family and also to estimate the prevalence of chlamydia in pregnant women. Material and methods. A prospective study was conducted in pregnant women > 16 years, in 2 large hospitals in Lima (Instituto Nacional Materno Perinatal y Hospital Arzobispo Loayza) during 2013. Chlamydia screening is offered to pregnant women during their first prenatal care using self-administered vaginal swabs (Aptima Combo 2 assay®, Hologic Gen-Probe). We contacted patients positive for Chlamydia within 14 days, they were given free counseling and directly observed treatment with azithrommycin 1 gram oral route to her and her partner. The pregnant women attending alone, were given 1 gram of azithrommycin to take home to your partner. A test of cure 3 weeks afte the treatment was performed.